HUMAN, WHO INVENTED MODERN SURGERY - Геник, С. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Literature review are submitted about the way of famous american surgeon Michael DeBeki and his success in the study problems of obliterative atherosclerosis, cardiovascular surgery and transplantology. The influence of his new developments and discoveries on effective treatment surgical diseases in the world are analyzed.